Students perception of teaching-learning methods in Community Medicine at a Government Medical College in Rajasthan - Sharma, Rupa; Yadav, Subhash Mohan; Joshi, Shree Mohan; Kaushik, Pratap Bhan (Indian Journal of Community Health, 2017)
Background: Knowledge of Community Medicine plays a pivot role in effective delivery of health care services. Effective Teaching-Learning (T-L) of a class of 150-200 students is a challenge. Research is needed to identify methods suitable to the needs of the students. Students’ perspective is an important diagnostic feedback tool in this context. Aims & Objectives: To know the students’ preferences and perceptions regarding current T-L methods and their felt need for modification in the T-L approach. Material & Methods: Responses were collected from students pursuing internship regarding their preferences and perception on a pretested, validated semi structured questionnaire, most of the responses were collected on a Likert type five point scale. The data was analyzed by calculating percentage, mean and Standard Deviation (SD). Result: Majority (66.2%) felt a need for modification in T-L Approach and 74% of these opined that it will improve their performance in assessments. Presentation of content was voted as most important component for effective T-L (mean 3.9± 1.39). Desirable modifications was more time allotment to integrated modular T-L (51%) and field visits (26%). Conclusion: A judicious combination of Power point presentations with Modular T-L sessions and Field visits can be a more effective T-L approach in Community Medicine from the students’ perspective.